Analisis Laporan Keuangan Dalam Memprediksi Kebangkrutan Dengan Model Springate Dan Model Grover Pada Perusahaan Pertambangan - Putu Rahadi Erawan; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the prediction of bankruptcy of mining companies listed on the BEI for the 2014-2018 period used the Springate and Grover model analysis method. The sample companies used in this study were 9 companies obtained by purposive sampling and observation for 5 years resulting in amount sample becomes 45 sample. The type of data used is secondary data, while the data collection techniques are obtained from historical data from mining companies, financial reports published by the BEI and literature studies. The data analysis technique used is the Springate model and the Grover model. The results of this study indicate that 1). The results of the analysis the Springate and Grover models can analyze the potential for financial distress well. 2). There are differences in the analysis of results between the two models and the Springate model is the most predictive in analyzing the potential for bankruptcy..